2017
DOI: 10.1002/jcp.26196
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing angiogenesis regulates the irradiation‐induced stimulation on osteoclastogenesis in vitro

Abstract: Ionizing radiation-induced bone loss is a potential health concern in radiotherapy, occupational exposure, and astronauts. Although impaired bone vasculature and reduced proliferation of bone-forming osteoblasts has been implicated in this process, it has not been clearly characterized that whether radiation affects the growth of bone-resorbing osteoclasts. The molecular crosstalk between different cell populations in the skeletal system has not yet been elucidated in detail, especially between the increased b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…RT‐induced osteitis and osteoradionecrosis result from altered blood supply to the bone and dysfunction of osteoblasts and osteoclasts 14 . Histopathology and pathogenesis of RT‐induced fibrosis is better studied in soft tissues than calvarial lesions.…”
Section: Discussionmentioning
confidence: 99%
“…RT‐induced osteitis and osteoradionecrosis result from altered blood supply to the bone and dysfunction of osteoblasts and osteoclasts 14 . Histopathology and pathogenesis of RT‐induced fibrosis is better studied in soft tissues than calvarial lesions.…”
Section: Discussionmentioning
confidence: 99%
“…But the combined use of BMP2/VEGF165 showed a much better effect in osseointegration, compared with HBO group, BMP2 group, and VEGF165 group. As discussed above, radiation would cause vascular damage, induce local microcirculation disorder, and decrease the expression of VEGF165 [15, 16, 29]. Schliephake reported that VEGF165 immobilized on the surface of titanium implants by using a modular binding system could enhance the contact rate between the bone and the implant surface to a certain extent [30].…”
Section: Discussionmentioning
confidence: 99%
“…VEGF165, a heparin-binding growth factor of VEGF family and the most active isoform of VEGF, acts as a mitogen of endothelial cells, a chemotactic mediator, and a vascular permeability inducer [14]. It plays a critical role in recruiting EPCs from the bone marrow, upregulating other angiogenic factors, promoting angiogenesis, and improving the formation of endothelium [15]. Evidence has shown that radiation treatment leads to vascular damage and reduces the expression of VEGF165.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tong and colleagues hypothesized that the effects of RT on bone marrow-derived endothelial progenitor cells may also impact the resorption of bone after RT. In an in vitro study, they found that RT induced substantial dysfunction in endothelial progenitor cells, including the downregulation of vascular endothelial growth factor A (VEGF-A), which is a potent angiogenic agent [83]. However, angiogenesis is a critical part of tumor growth and metastasis, and abnormally upregulated angiogenesis, specifically VEGF, is a direct target of many commonly used systemic therapy agents, including bevacizumab [84].…”
Section: Angiogenesis Manipulationmentioning
confidence: 99%